Russian Arctic Today: Substantive Novelties and Legal Collisions - Leksin, Vladimir Nikolaevich; Porfiriev, Boris Nikolaevich (Economy of Regions, 2018)
Recent changes in the Russian Arctic are often unique in terms of their nature and intensity. Fundamentally new production and infrastructure facilities are being launched, the innovative development of external defense facilities is being completed. Furthermore, the territories of corporate management and support zones for the development of Russian Arctic zone are being established. We consider the examples of the project in the South Tambey licensed area (a liquefied natural gas production facility, a large settlement, a seaport and a large airport), the construction of Rosneft's multifunctional service structure, changes in the nuclear power industry of the Chukotka Autonomous Okrug. Moreover, we demonstrate emerging legal collisions. A new edition of the state program for the Arctic regions development, and the establishment of eight support development zones on the territory of the Arctic zone was officially announced. We examine the primary changes in the organizational, managerial and legal support for the development of Russian Arctic zone, which are due to the above-mentioned legislative developments. We critically analyse plans to launch a State Governance Body, responsible for the significant part of the support zones, within the St. Petersburg administration. These and other novelties have required the revision of: a) the content of the federal law on the development of Russian Arctic zone, including in the context of foreign practice of implementing the «Arctic law»; b) a set of subordinate acts of the Russian Government, the state program «Socio-economic development of Russian Arctic for the period until 2020» in particular, which has been and will be substantially reconfigured in the near future.